2014
DOI: 10.1111/inm.12102
|View full text |Cite
|
Sign up to set email alerts
|

Handover of patient information from the crisis assessment and treatment team to the inpatient psychiatric unit

Abstract: Handover, or the communication of patient information between clinicians, is a fundamental component of health care. Psychiatric settings are dynamic environments relying on timely and accurate communication to plan care and manage risk. Crisis assessment and treatment teams are the primary interface between community and mental health services in many Australian and international health services, facilitating access to assessment, treatment, and admission to hospital. No previous research has investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 32 publications
0
16
0
10
Order By: Relevance
“…; Waters et al . ). There are also occasions where information is discussed that has been collaboratively obtained from other services and the patient's family without the patient's knowledge.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Waters et al . ). There are also occasions where information is discussed that has been collaboratively obtained from other services and the patient's family without the patient's knowledge.…”
Section: Discussionmentioning
confidence: 97%
“…This is consistent with research conducted both within mental health settings (Waters et al . ) and in general medicine (Drach‐Zahavy & Shilman ). Ultimately, health care has an increasing focus on efficiency, and health professionals are challenged to creatively find ways of working that maximize time, while delivering safe, effective care (Brunero & Lamont ; Lamont et al .…”
Section: Discussionmentioning
confidence: 99%
“…Handover is not simply about communication; it is crucial for care planning (Waters et al 2015). The participants in the present study wanted to know what decisions were being made, and how they could influence those decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding a consumer's perception of their general health, risk factors, and desire to change is also an important step for the road to recovery (Cleary et al 2013). Waters et al (2015) emphasized the importance of nursing handover in mental health to care planning.…”
Section: Introductionmentioning
confidence: 99%
“…Katschnig, for example, emphasized the importance of monitoring different levels of health care to find the best models or pathways of care. Waters et al suggested that documentation does not reflect patients' views on treatment. However, several studies have revealed that care pathways improve the components of care coordination …”
Section: Introductionmentioning
confidence: 99%